Calvatia guzmanii sp. nov. (Agaricaceae, Basidiomycota) from Paraná State, Brazil - Alves, Camila R.; Cortez, Vagner G. (Phytotaxa, 2013)
A new species of Calvatia is described from a semideciduous seasonal forest fragment in the western region of Paraná State, southern Brazil. Calvatia guzmanii is proposed as new based on the combination of dark brown and spiny to velvety exoperidium, prominent subgleba and echinulate-reticulate basidiospores with a short pedicel. A comparison with morphologically similar Calvatia species is giv